2009
DOI: 10.1111/j.1463-1318.2008.01670.x
|View full text |Cite
|
Sign up to set email alerts
|

The value of auditing negative lower GI investigations preceding a final diagnosis of colorectal cancer

Abstract: Colonoscopic miss rates are in line with previous studies. The application of simple clinical ground rules will avoid most pitfalls. The methodology described herein may assist in auditing the quality assurance of lower gastrointestinal diagnostic services. Despite the delay, late diagnosis was found to be associated with improved survival and a lower likelihood of metastatic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, colonoscopy is more costly and uncomfortable, although it also has good performance characteristics. 47 One hope was that CT colonography could replace colonoscopyhowever, it misses one in 10 of lesions larger than 1 cm -which are not missed by colonoscopy. 48 Also possible for the future are various biomarkers, 49 including a small protein, matrix metalloproteinase-9.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…However, colonoscopy is more costly and uncomfortable, although it also has good performance characteristics. 47 One hope was that CT colonography could replace colonoscopyhowever, it misses one in 10 of lesions larger than 1 cm -which are not missed by colonoscopy. 48 Also possible for the future are various biomarkers, 49 including a small protein, matrix metalloproteinase-9.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…A similar study by Somasekar et al ,16 found that 56 (10%) patients with a diagnosis of CRC had undergone barium enema (5%) or colonoscopy (5%) in the preceding 5 years. Another study by Frenette and Strum17 reported a failure of diagnosis in 60 (16%) patients who had undergone colonoscopy, barium enema or flexible sigmoidoscopy in the preceding 3 years.…”
Section: Discussionmentioning
confidence: 61%